Gambaran Kesehatan Mental pada Remaja Korban Toxic Parenting di Sidoarjo - Sanjaya, Frisca Aulia Permata; Wanesti, Nabilah Silvania; Lestari, Orchida Adi; Edy, Dewi Fatmasari (Universitas Negeri Malang, 2024)
Parents become the main foundation for children in the formation and development of children's character. Still, sometimes, there are children who grow up in conditions of parents who treat children harshly and arbitrarily to